Telemedicine transforming stroke care in Piauí: an analysis of a state-wide initiative's first year - Ricarte, Irapuá Ferreira; Sousa, Ícaro Araújo de; Neto, Romilto Costa Pacheco; Veras, Arthur de Oliveira; Silva, Camila Victória da; Mascarenhas, Cristina Calmon de Araújo; Silva, Matheus Felipe da; Silva, Gisele Sampaio; Pontes-Neto, Octávio Marques (Arquivos de Neuro-Psiquiatria, 2025)
Prior to October 2022, stroke patients in Piaui lacked access to both stroke unit care and thrombolytic treatment, until the implementation of a telemedicine-based stroke care program.To conduct a descriptive analysis of patients suspected of stroke who received telemedicine-based care in Piauí during the first year of the program's implementation.We conducted a retrospective analysis of 868 patients treated from October 2022 to September 2023 under the state-wide stroke care program, which includes 6 Stroke Treatment Centers distributed around the state. Utilizing data from the JOIN telemedicine platform, the analysis focused on patient demographics, stroke types, treatment timelines, and outcomes of thrombolytic treatment.The cohort included 868 patients, with a mean age of 67.2 years, out of whom 55.5% were male. Chronic hypertension was reported in 57.8% and diabetes in 22.5% of the patients. The average onset-to-door time was 3.3 hours, door-to-computed tomography time was 23 minutes, and door-to-needle time averaged 67 minutes. Thrombolysis was administered to 15.6% of all stroke cases, with 31.8% among those being ischemic strokes. Among patients who arrived within the thrombolytic time window, the rate was 27.3%.The introduction of a telemedicine-based stroke care program in Piauí has significantly enhanced access to essential stroke treatments, demonstrating its effectiveness in overcoming healthcare disparities. The initiative's success underscores the potential of telemedicine as a scalable model for improving stroke care in regions with limited healthcare resources. Future efforts will focus on reducing treatment times and expanding stroke care infrastructure to ensure comprehensive patient care.
Keywords: Stroke; Telemedicine; Thrombolytic Therapy; Healthcare Disparities; Brazil